The neutrophil-to-Lymphocyte ratio is associated with clinical symptoms in first-episode medication-naïve patients with schizophrenia - Xuan Wang; Xiaofang Chen; Xiaoni Guan; Zezhi Li (Schizophrenia, 2024)
Abstract Innate immunity has been shown to be associated with schizophrenia (Sch). This study explored the relationship between symptoms and neutrophil-to-lymphocyte ratio (NLR) (a marker of innate immunity) in patients with Sch. Ninety-seven first-episode medication-naïve (FEMN) patients with Sch and 65 healthy controls were recruited in this study. We measured the complete blood count and assessed the clinical symptoms using the PANSS scales. We found higher NEU counts and NLR in patients with Sch compared with control subjects. Male patients showed a higher NEU count than female patients. In addition, FEMN patients with higher NLR and NEU values showed higher PANSS-p, PANSS-g, and PANSS-total scores (all p < 0.05). Regression analysis revealed that NLR was a predictor for PANSS total scores in patients with Sch. Higher NLR value was observed in patients with Sch and the significant associations between NLR and psychotic symptoms indicate that an imbalance in inflammation and innate immune system may be involved in the pathophysiology of Sch.